The Effect of Teacher Competence and Work Motivation on Improving The Quality of Graduates - Nunti Sibuea; Winanda Marito; Achmad Deni; Ahmad Karim (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
The problems in this research are, How big is the influence of partial teacher competence through its dimensions on improving the quality of graduates at SMP Negeri Kisaran, Asahan Regency, How much influence does the teacher's work motivation partially through its dimensions have on improving the quality of graduates at SMPN, Asahan Regency and how big is the influence of teacher competence and teacher work motivation simultaneously through its dimensions on improving the quality of graduates at SMPN Asahan. The influence of teacher competence and teacher work motivation simultaneously through its dimensions on improving the quality of graduates at SMPN, Asahan. Research results: The results of the descriptive analysis of respondents showed that the respondents' responses to teacher competence were included in the good/medium category, namely 44%. Responses to work motivation are included in the good category by 38%. The response to the quality of graduates is included in the good category by 44%. Simultaneously, teacher competence and work motivation have a significant influence on the quality of graduates as evidenced by the SPSS 16.00 program, it can be seen that the calculated F value is 8.034 with sig. of 0.001 (p > 0.05). While the contribution of the variable Teacher Competence and Work Motivation to the quality of graduates is 0.327, which means the contribution of the variance provided by Teacher Competence and Work Motivation to the quality of graduates is 32.7%, while the remaining 67.3% is influenced by other variants outside the model.